Inhibitive Behaviour of Acacia senegalensis on Corrosion Resistance of Mild Steel-Acidic Environment - Suleiman, I.Y.; Yaro, S.A.; Abdulwahab, M. (Asian Journal of Chemistry, 2015)
The ethanolic extract of Acacia senegalensis (gum arabic) stem was used as corrosion inhibitor for mild steel in 0.5 M H2SO4 using gravimetric-weight loss and potentiodynamic polarization. The characterization of the coupon before and after the corrosion test was done using scanning electron microscopy equipped with energy dispersive X-ray spectroscopy (SEM/EDS). The temperature, inhibitor concentration and time were varied in the range of 30-70 °C at 20 °C interval, 0-10 % v/v at 2 % v/v interval and 45 to 270 min at 45 min interval, respectively. The synergetic effect of the inhibitor was evaluated by addition of halide ion (KI-). Corrosion rate increased with increase in temperature and decreased with increase in both inhibitor concentration and time. Inhibition efficiency was found to increase with increase in concentration of the extract and the maximum inhibition efficiency was found to be 94.16 %, maximum inhibition efficiency in the presence of KI was 99.62 % and was assumed to occur via adsorption of the inhibitor molecules on the metal surface. The adsorption of the molecules of the extract on the mild steel surface obey Langmuir adsorption isotherm. The potentiodynamic polarization results revealed that the extract acts as mixed type inhibitors.